2016
DOI: 10.1016/j.powtec.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic properties of reusable TiO 2 -loaded natural porous minerals in dye wastewater purification

Abstract: Diatomite-based recyclable photocatalysts containing single lanthanide doped TiO 2 nanoparticles (NPs) were synthesized by using simple sol-gel method. Photocatalytic activities of the prepared Ce-or La-single doped TiO 2 /diatomite catalysts were estimated by the degradation of Rhodamine B (RhB) under simulated sunlight irradiation. The XRD and Raman spectra shown only anatase phase of TiO 2 for the un-doped and Ce-doped samples. The TEM images revealed uniform distribution of TiO 2 NPs on the matrix, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…In contrast to previous studies [28][29][30][31][32][33][34], the photocatalytic activity in the present study continuously increased along with the PL intensity as the Si concentration in the β-Ga 2 O 3 nanofibers increased. This indicated that the mechanism of separation and recombination of photon-generated carriers alone was insufficient to explain the photocatalytic activity of the Si-doped β-Ga 2 O 3 nanofibers.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies [28][29][30][31][32][33][34], the photocatalytic activity in the present study continuously increased along with the PL intensity as the Si concentration in the β-Ga 2 O 3 nanofibers increased. This indicated that the mechanism of separation and recombination of photon-generated carriers alone was insufficient to explain the photocatalytic activity of the Si-doped β-Ga 2 O 3 nanofibers.…”
Section: Resultscontrasting
confidence: 99%
“…The photocatalytic activity of the β-Ga 2 O 3 nanofibers as shown in Figure 4 was correlated with both the PL and optical bandgap results in Figure 3. In previous reports where dopants were introduced in transparent conductive oxides (TCOs) such as Ce-doped TiO 2 [28], Hf-doped ZnO [29], Mg-doped ZnO [30], Al-doped ZnO [31], and Cu-doped TiO 2 [32], the photocatalytic activity of the TCOs increased, but the PL peak decreased with doping [33,34]. The enhancement of the photocatalytic activity caused by adding dopants was attributed to the higher separation efficiency of the photon-generated carriers-in other words, the lower recombination of electrons and holes due to the generated trap sites in the bandgap.…”
Section: Resultsmentioning
confidence: 99%
“…The nanocomposite, in addition to the ZnTiO 3 phase, consisted mainly of the anatase phase, whose characteristic peak appeared at 25.28° and, to a lesser extent, the rutile phase, whose characteristic peak appeared at 27.40° only for ZTO. This demonstrates that La-doping inhibited the transition of anatase to the rutile phase at the temperature–time conditions applied [ 2 ]. Furthermore, due to its low concentration, there were no diffraction peaks (50° and 60°) corresponding to the presence of La 2 O 3 oxide [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, water contamination by dyes has become one of the most important global concerns [ 1 , 2 ]. Currently, there are more than 10,000 types of commercial dyes available with an annual production of over 7 × 10 5 tons [ 3 ], and with a considerable fraction discharged from industries such as textile, paper, plastic, leather, ceramics, cosmetics, pharmaceuticals, and food processing [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the curve, the Ce doped Ba2TiMoO6 underwent decomposition at 600 and 720 °C (exothermic peaks) and 783.11 °C (endothermic peaks). After 910 °C, however, shows without weight loss is a result of the formation of the crystalline phase [49].…”
Section: Structur and Morphological Investigationmentioning
confidence: 99%